The family doctor - Instrumental in the development of the child (Portuguese Journal of Family Medicine and General Practice, 2009)
The health (wellness bio-psycho-social) and the experiences of the first years of life are critical determinants for the development and course of life of the individual.Despite decades in our country are characterized by frank improvement of health care for children, including the advancement of counseling and prenatal diagnosis with the consequent reduction in morbidity and mortality, there has been an increase in the prevalence of neurodevelopmental disorders.